Task Book PENGEMBANGAN BUKU TEKS BAHASA INDONESIA DENGAN MODEL SQ3R UNTUK KETERAMPILAN MEMBACA SISWA KELAS IV SD - Irinda Septiana (EduStream: Jurnal Pendidikan Dasar, 2022)
The purpose of this study is to develop a Indonesian text book SQ3R model for reading skill of 4th grade elementary school. There specific purpose of this study are: (1) to describe the development process SQ3R in Bahasa Indonesia Text Book for reading skill of grade IV student of Elementary School. (2) to describe the quality of book that has been developed. The quality of the book that has been developed, observed based on the product and the usage in the class. The research of this development based from four-D model that consist of (1) definition, (2) planning, (3) development, (4)dissemination. But, this research only reach the development step without disseminate, because it used in the trial school only, without disseminating in the other school. The data collection that has been conducted use documentation technique, observation, inquiry, and the test. The data collected, analyzed according qualitative-quantitative description method. Based from the research, resulted suitable presentation material 94, 4%, suitable presentation 96, 5%, suitable 94, 6%, suitable graphic90, 1%. From the result of the text book, it is very suitable categorized. The result of the observation of the teacher activity and student got 94, 3% presentation and 93, 8%. The teacher and student's respond got 87, 5% and 83%. Student's result increase become 16, 64 with the average 85, 2 that related with the final criteria, that is 75.